Research progress in ultra-high temperature thermal resistance coatings - LIU Dongrui; TANG Xing; XIAO Jie; GUO Qian; HE Wenting; GUO Hongbo (Cailiao gongcheng)
As the turbine inlet temperature in aero-engines continues to rise， conventional thermal barrier coatings （TBCs） are becoming increasingly ineffective at blocking thermal radiation in the near-infrared wavelength range generated by high-temperature gases. The heat transfer of heat radiation can penetrate through the coating and directly heat the underlying metal substrate， thereby compromising the service life of hot-end components. In this paper， the authors’ experimental results are used to review recent developments in the design of novel TBCs materials and structures that combine thermal insulation with enhanced radiation suppression capabilities. A comparative analysis of the near-infrared optical properties of conventional TBCs is presented. The current methods aimed at improving the ability of coatings to mitigate radiative heat transfer are discussed. Particular attention is given to the issue of conventional YSZ-based inability of TBCs to effectively block infrared radiation in the shortwave infrared region. An analysis is conducted on the two fundamental approaches for reducing the infrared transmittance of TBCs， namely， improving the infrared reflectance or infrared absorptance of coatings. Additionally， a systematic summary of the strategies for tuning the infrared reflectance and absorptance of coatings， including influencing factors， underlying mechanisms， advantages， and limitations， is provided. Finally， future trends and breakthrough directions in the development of novel radiation-suppressing coatings， particularly in terms of material and structural design as well as the use of high-performance computational tools， are highlighted.